Clinical Efficacy and In Vitro Drug Sensitivity Test Results of Azithromycin Combined With Other Antimicrobial Therapies in the Treatment of MDR P. aeruginosa Ventilator-Associated Pneumonia - Huang, Yuqin; Wang, Wenguo; Huang, Qiang; Wang, Zhengyan; Xu, Zhuanzhuan; Tu, Chaochao; Wan, Dongli; He, Miaobo; Yang, Xiaoyi; Xu, Huaqiang; Wang, Hanqin; Zhao, Ying; et al. (Frontiers in Pharmacology, 2022)
Objective: To study the effect of azithromycin (AZM) in the treatment of MDR P. aeruginosa VAP combined with other antimicrobial therapy. Methods: The clinical outcomes were retrospectively collected and analyzed to elucidate the efficacy of different combinations in the treatment of MDR-PA VAP. The minimal inhibitory concentration (MIC) of five drugs was measured by using agar dilution method against 27 isolates of MDR-PA, alone or in combination. Results: The incidence of VAP has approximately 10.4% (961/9245) in five years and 18.4% (177/961) caused by P. aeruginosa ranked fourth. 151 cases of MDR-P. aeruginosa were included in the clinical retrospective study. Clinical efficacy results: the MEM+AZM was 69.2% (9/13), the SCF+AZM was 60% (6/10), and the combinations of 3 drugs containing AZM was 69.2% (9/13). The curative effect of MEM+AMK was better than MEM+LEV group, P = 0.029 (P < 0.05). The curative effect of SCF+AMK was better than SCF+LEV group, P = 0.025 (P < 0.05). There was no significant difference between combinations of 2 or 3 drugs containing AZM，p>0.05（p=0.806）. From the MIC results, AMK single drug was already very sensitive to the selected strains. When MEM or SCF was combined with AZM, the sensitivity of them to strains can be significantly increased. After MEM+AZM, MIC50 and MIC90 of MEM decreased to 1 and 2 ug/mL from 8 and 32 ug/mL. After SCF+AZM, MIC50 decreased to 16 ug/mL, and the curve of SCF shifted obviously. After SCF + LEV + AZM, the MIC50 and MIC90 of SCF and LEV still could not achieve substantive changes. From the FIC index results, the main actions of MEM+AZM were additive effect, accounting for 72%; after the combination of SCF+AZM, the additive effect was 40%. AMK or LEV combined with AZM mainly showed unrelated effect, and the combination of three drugs could not improve the positive correlation between LEV and AZM. Conclusion: AZM may increase the effect of MEM and SCF against MDR-P. aeruginosa VAP. Based on MEM or SCF combined with AMK or AZM, can achieve a good effect in the treatment of MDR-P. aeruginosa VAP.